COVID-19 Vaccination in Lower-Middle Income Countries: National Stakeholder Views on Challenges, Barriers, and Potential Solutions - Tagoe, Eunice Twumwaa; Sheikh, Nurnabi; Morton, Alec; Nonvignon, Justice; Sarker, Abdur Razzaque; Williams, Lynn; Megiddo, Itamar (Frontiers in Public Health, 2021)
The development of COVID-19 vaccines does not imply the end of the global pandemic as now countries have to purchase enough COVID-19 vaccine doses and work towards their successful rollout. Vaccination across the world has progressed slowly in all but a few high-income countries (HICs) as governments learn how to vaccinate their entire populations amidst a pandemic. Most low- and middle-income countries (LMICs) have been relying on the COVID-19 Vaccines Global Access (COVAX) Facility to receive vaccines. COVAX aims to provide these countries enough doses to vaccinate twenty percent of their populations. LMICs will likely encounter additional barriers and challenges rolling out vaccines compared HICs despite their significant experience from the Expanded Programme on Immunization (EPI). This study explores potential barriers that will arise during COVID-19 vaccine rollout in lower-middle income countries and how to overcome them. We conducted sixteen semi-structured interviews with national-level stakeholders from Ghana and Bangladesh (eight in each country). Stakeholders included policymakers and immunization programme experts. Data were analysed using Framework Analysis. Stakeholders believed their country could use existing EPI structures for COVID-19 vaccine rollout despite existing challenges with the EPI and despite its focus on childhood immunization rather than vaccinating the entire population over a short period of time. Stakeholders suggested increasing confidence in the vaccine through community influencers and by utilising local government accredited institutions such as the Drug Authorities for vaccine approval. Additional strategies they discussed included training more health providers and recruiting volunteers to increase vaccination speed, expanding government budgets for COVID-19 vaccine purchase and delivery, and exploring other financing opportunities to address in-country vaccine shortages. Stakeholders also believed that LMICs may encounter challenges complying with priority lists. Our findings suggest that COVID-19 vaccination is different from previous vaccination programs, and therefore, policymakers have to expand the EPI structure and also take a systematic and collaborative approach to plan and effectively rollout the vaccines.